Digital marketing training to expand market reach for MSME in Kuala Jambi - Samsinar Samsinar; Rudolf Sinaga; Renny Afriany; Frangky Frangky (Universitas Muhammadiyah Magelang, 2024)
Digital marketing training for MSMEs in Kuala Jambi aims to enhance the knowledge and skills of MSME players in utilizing digital platforms and reaching a broader market. This activity involves a series of tailored training sessions designed to empower MSMEs with essential digital marketing skills. The method includes practical exercises on planning and implementing digital marketing strategies conducted by MSME owners participating in the training. The results of this activity offer valuable insights into the effectiveness of digital marketing training in expanding the market reach of MSMEs. The practical implications of this initiative provide a foundation for local governments, training institutions, and other stakeholders to develop more effective and sustainable training programs to support MSME growth in the digital era.